High-temperature-resistant silicon carbide ceramic membrane and preparation method thereof
Through the use of modified ammonium polyacrylate and modified talc powder, combined with specific sintering and coating layer construction processes, the existing silicon carbide ceramic film preparation methods and insufficient performance have been solved, and a silicon carbide ceramic film with high temperature resistance and excellent mechanical properties has been prepared, which is suitable for the application of a variety of high-performance materials.
Patent Information
- Application Number
- CN202510086997.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing silicon carbide ceramic membrane preparation methods are complex and are not suitable for promotional production. At the same time, there is a lack of materials that are resistant to high temperatures and excellent mechanical properties.
High temperature-resistant silicon carbide ceramic films are prepared by using raw materials such as modified ammonium polyacrylate and modified talc powder. The process includes the use of N,N-methylenebisacrylamide, diethylenetriamine, lauryl acrylate modified ammonium polyacrylate, chitosan modified talc, and improving the high temperature and mechanical properties of the ceramic film through high temperature sintering and uniform coverage of the coating layer.
The prepared silicon carbide ceramic membrane has good high temperature resistance and mechanical properties, and is suitable for the preparation of high temperature resistant materials, and can reach a high filtration accuracy of 0.1μm in filtration applications.
Smart Images

Figure BDA0005250390900000081 
Figure BDA0005250390900000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic membranes, and in particular relates to a high-temperature resistant silicon carbide ceramic membrane and a preparation method thereof. Background Art
[0002] Ceramic membrane separation technology is an efficient and energy-saving separation technology, and its application areas involve chemical industry, petroleum and petrochemical industry, biochemical industry, food, electronics, medicine and other industries. The ceramic membranes on the market are mainly made of aluminum oxide, titanium oxide, silicon oxide, zirconium oxide and silicon carbide. Among them, silicon carbide ceramic membranes have received high attention due to their excellent performance. They are mainly composed of silicon carbide ceramic support and silicon carbide membrane layer. Silicon carbide materials are widely used in functional ceramics, advanced refractory materials, mechanical seals, abrasives and metallurgical raw materials due to their high thermal conductivity, small thermal expansion coefficient, stable chemical properties, good wear resistance, high hardness and chemical corrosion resistance.
[0003] The Chinese patent CN 109824381 B relates to a silicon carbide ceramic membrane and its preparation method and use, wherein the silicon carbide ceramic membrane comprises a support and a pure silicon carbide membrane layer uniformly attached to the support, wherein the membrane layer is composed of interconnected silicon carbide fibers, and the preparation method of the silicon carbide ceramic membrane comprises the following steps: applying dispersion A on the surface of the silicon carbide support and drying to obtain a prefabricated membrane, applying silicon monoxide dispersion on the surface of the prefabricated membrane and drying to obtain a reaction membrane, calcining the reaction membrane under vacuum conditions to obtain a porous ceramic membrane preform, and treating the ceramic membrane preform with acid or alkali, and then calcining in air or oxygen atmosphere. However, the preparation method still requires further treatment with acid or alkali, and the process is relatively complicated, which is not suitable for promotion and production.
[0004] Therefore, the present invention aims to provide a silicon carbide ceramic membrane with a relatively simple production process, while making it have both high temperature resistance and excellent mechanical properties. Summary of the invention
[0005] In view of the existing technical problems, the purpose of the present invention is to provide a high-temperature resistant silicon carbide ceramic membrane and a preparation method thereof. The ceramic membrane of the present invention has good high-temperature resistance and excellent mechanical properties, can be used to prepare high-temperature resistant materials, and has good application value.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] On the one hand, the present invention provides a high-temperature resistant silicon carbide ceramic membrane, which comprises a silicon carbide support and a coating layer in sequence; the silicon carbide support comprises the following raw materials, measured by weight: 80-100 parts of a first silicon carbide powder, 3-5 parts of a sintering aid, 5-10 parts of polyvinyl alcohol, 2-3 parts of modified ammonium polyacrylate, and 0.1-0.4 parts of dibutyl phthalate.
[0008] The reaction mechanism and effects of the present invention are as follows:
[0009] 1. Ammonium polyacrylate has unique steric stabilization mechanism and electrostatic stabilization mechanism, which can effectively adjust the viscosity and stability of ceramic slurry, thereby helping to improve the performance of the final product. However, ammonium polyacrylate is hydrophilic, which is not conducive to its application in silicon carbide ceramic membranes that require high temperature resistance.
[0010] The applicant introduced N,N-methylenebisacrylamide, diethylenetriamine, and lauryl acrylate to modify ammonium polyacrylate. On the one hand, the copolymerization of lauryl acrylate and ammonium polyacrylate will increase the hydrophobicity of the polymer, improve its compatibility with non-polar substances, and also increase the mechanical properties and high temperature resistance of the polymer; on the other hand, the introduction of N,N-methylenebisacrylamide and diethylenetriamine can increase the crosslinking degree of the polymer, thereby improving the mechanical strength, chemical stability and high temperature resistance of the silicon carbide support.
[0011] 2. Talc is stable at high temperatures, not easy to decompose, and chemically inert. It also has the function of improving mechanical properties. However, it is difficult to disperse evenly in water and is prone to agglomeration.
[0012] The present invention introduces chitosan to modify talc. First, chitosan can be adsorbed and interspersed on the surface and inside of talc, reducing the tendency of talc to agglomerate. Second, chitosan contains abundant functional groups (such as amino, hydroxyl, etc.) that can form hydrogen bonds with hydroxyl groups in the second silicon carbide powder, further improving the dispersibility of the second silicon carbide powder. Next, the applicant introduces 3-trimethoxysilane acrylate and N-allyl-N-methylpyrrolidine chloride to modify the pre-treated talc. The use of 3-trimethoxysilane acrylate makes the talc have good dispersion uniformity, ensuring the performance of the coating layer; in addition, N-allyl-N-methylpyrrolidine chloride will have a strong interaction with the hydroxyl groups on the surface of the first silicon carbide, so that the coating layer formed after the modified talc can be evenly coated on the surface of the silicon carbide support, thereby making the silicon carbide support highly densified, further improving the overall mechanical properties and high temperature resistance of the silicon carbide ceramic film.
[0013] In some embodiments, the coating layer comprises the following raw materials, measured in parts by weight: 20-30 parts of second silicon carbide powder, 5-10 parts of modified talc powder, 2-4 parts of polyvinyl pyrrolidone, and 50-70 parts of deionized water.
[0014] Preferably, the average particle size of the first silicon carbide powder is 40-60 μm, and the average particle size of the second silicon carbide powder is 2-8 μm.
[0015] In some embodiments, the sintering aid is a mixture of alumina and titania.
[0016] Preferably, the mass ratio of aluminum oxide to titanium dioxide is 3:(1.5-2).
[0017] In some embodiments, the method for preparing the modified ammonium polyacrylate comprises the following steps:
[0018] Ammonium polyacrylate, N,N-methylenebisacrylamide, diethylenetriamine, lauryl acrylate and deionized water are mixed, placed at 50-60° C. for 30-40 minutes, vacuum homogenized, and vacuum spray dried to obtain modified ammonium polyacrylate.
[0019] In some embodiments, the vacuum homogenization conditions are: controlling the vacuum degree to 0.04-0.06 MPa, the rotation speed to 2000-2600 rpm, and the homogenization time to 15-25 min.
[0020] In some embodiments, the mass ratio of the ammonium polyacrylate, N,N-methylenebisacrylamide, diethylenetriamine, and lauryl acrylate is 1:(0.3-0.5):(0.7-0.9):(0.2-0.4).
[0021] In some embodiments, the method for preparing the modified talc comprises the following steps:
[0022] Q1. Mix talc, chitosan, and 2-3wt% acetic acid aqueous solution, stir for 2-4h, filter, wash, and dry to obtain pretreated talc;
[0023] Q2. The pretreated talc obtained in step Q1, 3-trimethoxysilane acrylate, water and ethanol are mixed, heated to 60-70°C for reaction for 5-6 hours, N-allyl-N-methylpyrrolidone chloride and azobisisobutyronitrile are added, the reaction is kept warm for 2-3 hours, washed and dried to obtain modified talc.
[0024] In some embodiments, the mass ratio of talc to chitosan in step Q1 is 1:(0.3-0.5).
[0025] In some embodiments, the mass ratio of the pretreated talc, 3-trimethoxysilane acrylate, and N-allyl-N-methylpyrrolidino chloride in step Q2 is 1:(0.3-0.5):(0.25-0.4).
[0026] Another aspect of the present invention provides a method for preparing a high temperature resistant silicon carbide ceramic film, comprising the following steps:
[0027] S1. The first silicon carbide powder, sintering aid, polyvinyl alcohol, modified ammonium polyacrylate, dibutyl phthalate were mixed, stirred for 1-2h, ball milled for 5-6h, extruded, heated to 300-350°C at a heating rate of 1-3°C / min, then heated to 600-620°C at a heating rate of 2-4°C / min, maintained for 1-2h, and then heated to 1400-1500°C at a heating rate of 3-5°C / min, maintained for 2.5-3.5h, and cooled to obtain a silicon carbide support;
[0028] S2. The second silicon carbide powder, modified talc, polyvinyl pyrrolidone, deionized water were mixed and stirred for 1-1.5h to obtain a coating layer raw material;
[0029] S3. The surface of the silicon carbide support obtained in step S1 is coated with the coating layer raw material obtained in step S2, and the temperature is increased to 1400-1500° C. at a heating rate of 3-5° C. / min, and maintained for 2.5-3.5 hours to obtain a silicon carbide ceramic film.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The ceramic membrane of the present invention has good high temperature resistance and excellent mechanical properties, and can be used to prepare high temperature resistant materials, and has good application value. When the ceramic membrane is used as a filter membrane, its filtration accuracy can reach up to 0.1 μm.
[0032] (2) The present invention introduces N,N-methylenebisacrylamide, diethylenetriamine, and lauryl acrylate to modify ammonium polyacrylate. On the one hand, the copolymerization of lauryl acrylate and ammonium polyacrylate increases the hydrophobicity of the polymer, improves its compatibility with non-polar substances, and also increases the mechanical properties and high temperature resistance of the polymer; on the other hand, the introduction of N,N-methylenebisacrylamide and diethylenetriamine can increase the crosslinking degree of the polymer, thereby improving the mechanical strength, chemical stability, and high temperature resistance of the silicon carbide support.
[0033] (3) On the one hand, the modified talc powder of the present invention can reduce the agglomeration tendency of talc powder, thereby ensuring the performance of the coating layer; on the other hand, chitosan contains abundant functional groups that can form hydrogen bonds with groups such as hydroxyl groups in the second silicon carbide powder, thereby further improving the dispersibility of the second silicon carbide powder; in addition, N-allyl-N-methylpyrrolidone chloride will have a strong interaction with the hydroxyl groups on the surface of the first silicon carbide, so that the coating layer formed after the modified talc powder can be evenly coated on the surface of the silicon carbide support, thereby further improving the overall mechanical properties and high temperature resistance of the silicon carbide ceramic film. DETAILED DESCRIPTION
[0034] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, rather than to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0035] According to the ratios and preparation methods of the raw materials specified in the following examples and comparative examples, various ceramic membranes were prepared. In order to facilitate those skilled in the art to implement the present invention, some of the raw material manufacturers of the examples and comparative examples are described as follows:
[0036] Polyvinyl alcohol: purchased from Wuhan Runxingyuan Technology Co., Ltd., model 1788;
[0037] Polyvinyl pyrrolidone: purchased from Huzhou Shenhua Polymer Materials Co., Ltd., model K30;
[0038] Ammonium polyacrylate: purchased from Wuhan Meiqilin New Materials Co., Ltd., model 568a;
[0039] Chitosan: purchased from Qingdao Bozhihuili Biotechnology Co., Ltd.;
[0040] The average particle size of the first silicon carbide powder is 50 μm; the average particle size of the second silicon carbide powder is 5 μm;
[0041] Other related raw materials are not specially specified and can be purchased from the market.
[0042] Preparation Example 1
[0043] The preparation method of modified ammonium polyacrylate A comprises the following steps:
[0044] 100 g of ammonium polyacrylate, 40 g of N,N-methylenebisacrylamide, 80 g of diethylenetriamine, 28 g of lauryl acrylate and 2 L of deionized water were mixed, placed at 55° C. for 40 min, vacuum homogenized, the vacuum degree was controlled at 0.05 MPa, the rotation speed was 2400 rpm, the homogenization time was 20 min, vacuum spray dried, the vacuum degree was controlled at 0.06 MPa, the atomization pressure was 0.5 MPa, the inlet temperature was 100° C., and the outlet temperature was 40° C. to obtain modified ammonium polyacrylate A.
[0045] Preparation Example 2
[0046] The preparation method of modified ammonium polyacrylate B is the same as that of Preparation Example 1, except that the amount of lauryl acrylate added is 27 g.
[0047] Preparation Example 3
[0048] The preparation method of modified ammonium polyacrylate C is the same as that of Preparation Example 1, except that the added amount of N,N-methylenebisacrylamide is 67 g.
[0049] Preparation Example 4
[0050] The preparation method of modified talcum powder A comprises the following steps:
[0051] Q1. 30 g of talc, 12 g of chitosan, and 200 mL of a 2.5 wt% aqueous solution of acetic acid were mixed, stirred for 3 h, filtered, washed three times with deionized water, and dried at 85 ° C for 4 h to obtain pretreated talc;
[0052] Q2. Mix 20 g of pretreated talc obtained in step Q1, 8 g of 3-trimethoxysilane acrylate, 300 mL of water, and 200 mL of ethanol, heat to 65 ° C for reaction for 5.5 h, add 6 g of N-allyl-N-methylpyrrolidone chloride and 0.1 g of azobisisobutyronitrile, keep warm for 2.5 h, wash once with deionized water and anhydrous ethanol, and dry at 85 ° C to constant weight to obtain modified talc A.
[0053] Preparation Example 5
[0054] The preparation method of modified talc B is the same as that of Preparation Example 4, except that the amount of chitosan added in step Q1 is 8.2 g.
[0055] Preparation Example 6
[0056] The preparation method of modified talc powder C is the same as that of Preparation Example 4, except that the amount of talc powder of 3-trimethoxysilane acrylate propyl added in step Q2 is 5.6 g.
[0057] Preparation Example 7
[0058] The preparation method of modified talc D is the same as that of Preparation Example 4, except that the amount of N-allyl-N-methylpyrrolidine chloride added in step Q2 is 4.4 g.
[0059] Example 1
[0060] A high-temperature resistant silicon carbide ceramic membrane, which comprises a silicon carbide support and a coating layer in sequence; the silicon carbide support comprises the following raw materials, by weight: 90 parts of a first silicon carbide powder, 4 parts of a sintering aid, 7.5 parts of polyvinyl alcohol, 2.5 parts of modified ammonium polyacrylate A, and 0.25 parts of dibutyl phthalate; the coating layer comprises the following raw materials: 25 parts of a second silicon carbide powder, 7.5 parts of modified talc A, 3 parts of polyvinyl pyrrolidone, and 60 parts of deionized water; wherein the sintering aid is a mixture of aluminum oxide and titanium dioxide, and the mass ratio of the two is 3:1.75.
[0061] The method for preparing the silicon carbide ceramic film of this embodiment comprises the following steps:
[0062] S1. The first silicon carbide powder, sintering aid, polyvinyl alcohol, modified ammonium polyacrylate A, and dibutyl phthalate were mixed, stirred for 1.5 hours, ball-milled for 5.5 hours, extruded, heated to 330°C at a heating rate of 2°C / min, then heated to 610°C at a heating rate of 3°C / min, maintained for 1.5 hours, and then heated to 1450°C at a heating rate of 4°C / min, maintained for 3 hours, and cooled to room temperature to obtain a silicon carbide support;
[0063] S2. The second silicon carbide powder, modified talc A, polyvinyl pyrrolidone, deionized water were mixed and stirred for 1h to obtain a coating layer raw material;
[0064] S3. The surface of the silicon carbide support obtained in step S1 is coated with the coating layer raw material obtained in step S2, and the temperature is increased to 1450° C. at a heating rate of 4° C. / min and maintained for 3 hours to obtain a silicon carbide ceramic film.
[0065] Example 2
[0066] A high-temperature resistant silicon carbide ceramic membrane, which comprises a silicon carbide support and a coating layer in sequence; the silicon carbide support comprises the following raw materials, by weight: 80 parts of a first silicon carbide powder, 3 parts of a sintering aid, 5 parts of polyvinyl alcohol, 2 parts of modified ammonium polyacrylate A, and 0.1 parts of dibutyl phthalate; the coating layer comprises the following raw materials: 20 parts of a second silicon carbide powder, 5 parts of modified talc A, 2 parts of polyvinyl pyrrolidone, and 50 parts of deionized water; wherein the sintering aid is a mixture of aluminum oxide and titanium dioxide, and the mass ratio of the two is 2:1.
[0067] The method for preparing the silicon carbide ceramic film of this embodiment comprises the following steps:
[0068] S1. The first silicon carbide powder, sintering aid, polyvinyl alcohol, modified ammonium polyacrylate A, and dibutyl phthalate were mixed, stirred for 1 h, ball milled for 5 h, extruded, heated to 300 ° C at a heating rate of 1 ° C / min, then heated to 600 ° C at a heating rate of 2 ° C / min, maintained for 1 h, and then heated to 1400 ° C at a heating rate of 3 ° C / min, maintained for 2.5 h, and cooled to room temperature to obtain a silicon carbide support;
[0069] S2. The second silicon carbide powder, modified talc A, polyvinyl pyrrolidone, deionized water were mixed and stirred for 1h to obtain a coating layer raw material;
[0070] S3. The surface of the silicon carbide support obtained in step S1 is coated with the coating layer raw material obtained in step S2, and the temperature is increased to 1400° C. at a heating rate of 3° C. / min and maintained for 2.5 hours to obtain a silicon carbide ceramic film.
[0071] Example 3
[0072] A high-temperature resistant silicon carbide ceramic membrane, which comprises a silicon carbide support and a coating layer in sequence; the silicon carbide support comprises the following raw materials, by weight: 100 parts of a first silicon carbide powder, 5 parts of a sintering aid, 10 parts of polyvinyl alcohol, 3 parts of modified ammonium polyacrylate A, and 0.4 parts of dibutyl phthalate; the coating layer comprises the following raw materials: 30 parts of a second silicon carbide powder, 10 parts of modified talc A, 4 parts of polyvinyl pyrrolidone, and 70 parts of deionized water; wherein the sintering aid is a mixture of aluminum oxide and titanium dioxide, and the mass ratio of the two is 1.5:1.
[0073] The method for preparing the silicon carbide ceramic film of this embodiment comprises the following steps:
[0074] S1. The first silicon carbide powder, sintering aid, polyvinyl alcohol, modified ammonium polyacrylate A, and dibutyl phthalate were mixed, stirred for 2 hours, ball-milled for 6 hours, extruded, and heated to 350°C at a heating rate of 3°C / min, then heated to 620°C at a heating rate of 4°C / min, maintained for 2 hours, and then heated to 1500°C at a heating rate of 5°C / min, maintained for 3.5 hours, and cooled to room temperature to obtain a silicon carbide support;
[0075] S2. The second silicon carbide powder, modified talc A, polyvinyl pyrrolidone, deionized water were mixed and stirred for 1.5h to obtain a coating layer raw material;
[0076] S3. The surface of the silicon carbide support obtained in step S1 is coated with the coating layer raw material obtained in step S2, and the temperature is increased to 1500° C. at a heating rate of 5° C. / min and maintained for 3.5 hours to obtain a silicon carbide ceramic film.
[0077] Example 4
[0078] A high temperature resistant silicon carbide ceramic membrane and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that modified ammonium polyacrylate B is used instead of modified ammonium polyacrylate A.
[0079] Example 5
[0080] A high temperature resistant silicon carbide ceramic membrane and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that modified ammonium polyacrylate C is used instead of modified ammonium polyacrylate A.
[0081] Example 6
[0082] A high temperature resistant silicon carbide ceramic membrane and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that modified talcum powder B is used instead of modified talcum powder A.
[0083] Example 7
[0084] A high temperature resistant silicon carbide ceramic membrane and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that modified talcum powder C is used instead of modified talcum powder A.
[0085] Example 8
[0086] A high temperature resistant silicon carbide ceramic membrane and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that modified talcum powder D is used instead of modified talcum powder A.
[0087] Comparative Example 1
[0088] A high temperature resistant silicon carbide ceramic membrane and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that commercially available ammonium polyacrylate 568a is used instead of modified ammonium polyacrylate A.
[0089] Comparative Example 2
[0090] A high temperature resistant silicon carbide ceramic membrane and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that commercially available talcum powder is used instead of modified talcum powder A.
[0091] Effect evaluation:
[0092] Ceramic membranes were prepared according to the above-mentioned Examples 1-8 and Comparative Examples 1-2, and tested. The specific test methods are as follows, and the test results are shown in Table 1.
[0093] Performance Test:
[0094] (1) Compressive strength: Referring to GB / T 4740-1999 Test method for compressive strength of ceramic materials, the compressive strength of a 30 mm × 5 mm × 6 mm strip silicon carbide ceramic membrane was tested;
[0095] (2) High temperature resistance: A 30 mm × 5 mm × 6 mm strip silicon carbide ceramic membrane was placed in a high temperature treatment at 850 °C for 1 hour, and then cooled and tested for its compressive strength using the above method.
[0096] Table 1 Performance test
[0097]
[0098]
[0099] The ceramic membranes prepared in Examples 1-3 of the present invention have good compressive strength and high temperature resistance.
[0100] Compared with Example 1, Example 4-5 changed the mass ratio of ammonium polyacrylate, N,N-methylenebisacrylamide, diethylenetriamine, and lauryl acrylate when preparing modified ammonium polyacrylate. Example 4 weakened the compatibility, and Example 5 changed the degree of crosslinking, both of which reduced the compressive strength and high temperature resistance of the ceramic membrane.
[0101] Compared with Example 1, when preparing modified talc powder, Example 6-8 changes the mass ratio of talc powder and chitosan, and the dispersibility of talc powder and the second silicon carbide powder will be weakened. Examples 7-8 change the mass ratio of pretreated talc powder, 3-trimethoxysilane acrylate, and N-allyl-N-methylpyrrolidone chloride, so that the dispersibility of talc powder is weakened and the degree of densification is reduced, which will affect the compressive strength and high temperature resistance of the ceramic membrane.
[0102] In comparative example 1, commercially available ammonium polyacrylate was used to replace modified ammonium polyacrylate A, and in comparative example 2, commercially available talcum powder was used to replace modified talcum powder A, both of which would reduce the compressive strength and high temperature resistance of the ceramic membrane.
[0103] The above is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present application. Although the present application is disclosed as above in the preferred embodiment, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution.
Claims
1. A high temperature resistant silicon carbide ceramic membrane, characterized in that: The silicon carbide ceramic film comprises a silicon carbide support and a coating layer in sequence; the silicon carbide support comprises the following raw materials in parts by weight: 80-100 parts of first silicon carbide powder, 3-5 parts of sintering aid, 5-10 parts of polyvinyl alcohol, 2-3 parts of modified ammonium polyacrylate, and 0.1-0.4 parts of dibutyl phthalate.
2. A high temperature resistant silicon carbide ceramic membrane according to claim 1, characterized in that: The coating layer comprises the following raw materials in parts by weight: 20-30 parts of second silicon carbide powder, 5-10 parts of modified talc powder, 2-4 parts of polyvinyl pyrrolidone, and 50-70 parts of deionized water.
3. The high temperature resistant silicon carbide ceramic membrane according to claim 1, characterized in that: The sintering aid is a mixture of aluminum oxide and titanium dioxide.
4. The high temperature resistant silicon carbide ceramic membrane according to claim 1, characterized in that: The preparation method of the modified ammonium polyacrylate comprises the following steps: Ammonium polyacrylate, N,N-methylenebisacrylamide, diethylenetriamine, lauryl acrylate and deionized water are mixed, placed at 50-60° C. for 30-40 minutes, vacuum homogenized, and vacuum spray dried to obtain modified ammonium polyacrylate.
5. The high temperature resistant silicon carbide ceramic membrane according to claim 4, characterized in that: The vacuum homogenization conditions are as follows: the vacuum degree is controlled to be 0.04-0.06 MPa, the rotation speed is 2000-2600 rpm, and the homogenization time is 15-25 min.
6. The high temperature resistant silicon carbide ceramic membrane according to claim 4, characterized in that: The mass ratio of the ammonium polyacrylate, N,N-methylenebisacrylamide, diethylenetriamine and lauryl acrylate is 1:(0.3-0.5):(0.7-0.9):(0.2-0.4).
7. The high temperature resistant silicon carbide ceramic membrane according to claim 1, characterized in that: The preparation method of the modified talcum powder comprises the following steps: Q1. Mix talc, chitosan, and 2-3wt% acetic acid aqueous solution, stir for 2-4h, filter, wash, and dry to obtain pretreated talc; Q2. The pretreated talc obtained in step Q1, 3-trimethoxysilane acrylate, water and ethanol are mixed, heated to 60-70°C for reaction for 5-6 hours, N-allyl-N-methylpyrrolidone chloride and azobisisobutyronitrile are added, the reaction is kept warm for 2-3 hours, washed and dried to obtain modified talc.
8. The high temperature resistant silicon carbide ceramic membrane according to claim 7, characterized in that: The mass ratio of talc to chitosan in step Q1 is 1:(0.3-0.5).
9. The high temperature resistant silicon carbide ceramic membrane according to claim 7, characterized in that: The mass ratio of the pretreated talc powder, 3-trimethoxysilane acrylate, and N-allyl-N-methylpyrrolidino chloride in step Q2 is 1:(0.3-0.5):(0.25-0.4).
10. A method for preparing a high temperature resistant silicon carbide ceramic film according to any one of claims 1 to 9, characterized in that: The following steps are included: S1. The first silicon carbide powder, sintering aid, polyvinyl alcohol, modified ammonium polyacrylate, dibutyl phthalate were mixed, stirred for 1-2h, ball milled for 5-6h, extruded, heated to 300-350°C at a heating rate of 1-3°C / min, then heated to 600-620°C at a heating rate of 2-4°C / min, maintained for 1-2h, and then heated to 1400-1500°C at a heating rate of 3-5°C / min, maintained for 2.5-3.5h, and cooled to obtain a silicon carbide support; S2. The second silicon carbide powder, modified talc, polyvinyl pyrrolidone, deionized water were mixed and stirred for 1-1.5h to obtain a coating layer material; S3. The surface of the silicon carbide support obtained in step S1 is coated with the coating layer raw material obtained in step S2, and the temperature is increased to 1400-1500° C. at a heating rate of 3-5° C. / min, and maintained for 2.5-3.5 hours to obtain a silicon carbide ceramic film.
Citation Information
Patent Citations
A silicon carbide ceramic membrane, its preparation method and applications
CN109824381B
Thickening agent and preparation method thereof
CN102964504A
Silicon carbide ceramic membrane and preparation method thereof
CN105130441A
Preparation method of high-strength uniform-hole silicon carbide ceramic membrane
CN105175005A
Preparation method of porous silicon carbide slab ceramic membrane
CN108704492A